(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The present study was designed impact of the right to education act (RTE), 2009 on the awareness and attitudes of teachers and parents in rural and urban areas of Meerut district .The sample for the present study consisted of 200 teachers and parents of rural and urban area selected randomly from the different schools in Meerut district of Uttar Pradesh. The result revealed that to the inference that there is significant difference between the rural and urban teachers in their awareness towards RTE Act 2009. Urban parents possess significantly more aware towards RTE Act 2009 than the rural parents. This result leads us to inference that urban teachers possess significantly more positive attitude towards RTE Act 2009 Than the rural teachers this result leads us to inference that urban parents possess significantly more positive attitude towards RTE Act 2009 Than the rural parents.